Healing the Past by Nurturing the Future—co-designing perinatal strategies for Aboriginal and Torres Strait Islander parents experiencing complex trauma: framework and protocol for a community-based participatory action research study. Issue 6 (11th June 2019) - Chamberlain, Catherine; Gee, Graham; Brown, Stephanie Janne; Atkinson, Judith; Herrman, Helen; Gartland, Deirdre; Glover, Karen; Clark, Yvonne; Campbell, Sandra; Mensah, Fiona K; Atkinson, Caroline; Brennan, Sue E; et al.
Abstract : Introduction: Child maltreatment and other traumatic events can have serious long-term physical, social and emotional effects, including a cluster of distress symptoms recognised as 'complex trauma'. Aboriginal and Torres Strait Islander (Aboriginal) people are also affected by legacies of historical trauma and loss. Trauma responses may be triggered during the transition to parenting in the perinatal period. Conversely, becoming a parent offers a unique life-course opportunity for healing and prevention of intergenerational transmission of trauma. This paper outlines a conceptual framework and protocol for an Aboriginal-led, community-based participatory action research (action research) project which aims to co-design safe, acceptable and feasible perinatal awareness, recognition, assessment and support strategies for Aboriginal parents experiencing complex trauma. Methods and analysis: This formative research project is being conducted in three Australian jurisdictions (Northern Territory, South Australia and Victoria) with key stakeholders from all national jurisdictions. Four action research cycles incorporate mixed methods research activities including evidence reviews, parent and service provider discussion groups, development and psychometric evaluation of a recognition and assessment process and drafting proposals for pilot, implementation and evaluation. Reflection and planning stages of four action research cycles will be undertaken in four key stakeholder workshops aligned with the first four Intervention Mapping steps to prepare programme plans. Ethics and dissemination: Ethics and dissemination protocols are consistent with the National Health and Medical Research Council Indigenous Research Excellence criteria of engagement, benefit, transferability and capacity-building. A conceptual framework has been developed to promote the application of core values of safety, trustworthiness, empowerment, collaboration, culture, holism, compassion and reciprocity. These include related principles and accompanying reflective questions to guide research decisions.